eCOMMUNICATION IN eLEARNING - Cimermanova, Ivana (European Scientific Journal, ESJ, 2013)
The article brings several opinion on application e-learning tools in mostly face-to-face formal teaching. It especially focusses on different types of interactions: interactions among students, students and teacher, interaction with materials and objects, but also, visual representations, etc. Interaction Design is a discipline present since 1980s and it deals with "shaping digital things for people’s use". Many online course designers build their courses intuitively without having computational background and digital pedagogy background. Not all “traditional” teachers are ready to build and run e-courses is what practice shows. The author analyses the survey and interviews realized with e-tutor and e-students and suggests the ways how to help teachers to create more interactive courses.